Analisis Penilaian Makro untuk Arsip di PT. Kereta Api Indonesia Daerah Operasi 7 Madiun - Fajriyah, Annisa; Azis, Muhammad Imam (Khazanah: Jurnal Pengembangan Kearsipan, 2024)
Macro appraisal is one approach in determining the value of archives, which is closely related to the use value and future depreciation of archives. This research was conducted to identify archives using a macro assessment based on analysis of the implementation of organizational functions to identify then the values to produce a list of vital records within the PT. Kereta Api Indonesia (Persero) Operation Area 7 Madiun. The method used in this research is a qualitative approach by collecting data through interviews in the archives section and units at PT. Kereta Api Indonesia (Persero) Operation Area 7 Madiun. Apart from that, searching documents related to the implementation of main tasks and functions of each archive creation unit is also part of this research method. Data analysis was carried out using the macro archive assessment method, namely analyzing the main tasks and functions of each archive creator's unit and continuing with legal and risk analysis. The results show that from 18 archive creation units produced a total of 195 records, with 112 of them based on the analysis results identified as vital records. These results can be input for relevant agencies to carry out special maintenance and treatment, especially as vital records.